The eleventh victim - Grace, Nancy, 1959- (Hyperion, 2009)
Psychology student Hailey Dean's fiancé was murdered. Hailey becomes a lawyer in Atlanta and fights back by prosecuting violent crime. However, years of courtroom battles and an endless tide of victims have taken their toll, and the trial of a serial killer who targeted young prostitutes will be her last. After starting over in Manhattan as a therapist, she is forced to match wits with someone who is brutally murdering her clients one by one, using a copycat M.O. as the Atlanta killer she had hunted down years before. Can she get to the killer before more innocent people die?--From publisher description.